Interactions between Stress and Vestibular Compensation – A Review - Saman, Yougan; Bamiou, Doris; Gleeson, Michael; Dutia, Mayank B. (Frontiers in Neurology, 2012)
Elevated levels of stress and anxiety often accompany vestibular dysfunction, while conversely complaints of dizziness and loss of balance are common in patients with panic and other anxiety disorders. The interactions between stress and vestibular function, and plasticity have been investigated both in animal models and in clinical studies. Evidence from animal studies indicates that vestibular symptoms are effective in activating the stress axis, and that the acute stress response is important in promoting compensatory synaptic and neuronal plasticity in the vestibular system and cerebellum. The role of stress in human vestibular disorders is complex, and definitive evidence is lacking. This article reviews the evidence from animal and clinical studies with a focus on the effects of stress on the central vestibular pathways and their role in the pathogenesis and management of human vestibular disorders.